The tanaidacean assemblage from the Central Pacific Manganese Nodule Province. II. The genera Stenotanais and Typhlotanais (Crustacea) - Larsen, Kim (Zootaxa, 2011)
Three new species of Tanaidacea are described from the manganese nodule province between the Clarion and the Clipperton Fracture Zone of the equatorial North Pacific Ocean. The specimens were collected during the Nodinaut expedition on board the r/v l´Atalante in the summer of 2004. The new species belongs to the genera Stenotanais (S. arenasi) and Typhlotanais (T. froufesae, T. pereosetulosa). Stenotanais arenasi is believed to be the first male Stenotanais reported. A key to the genus Stenotanais is presented. The anterior pleopods of T. pereosetulosa were found to be dissimilar from the posterior.